Effectiveness of an extracurricular program for struggling readers: A comparative study with parent tutors and volunteer tutors. (April 2019) - Villiger, Caroline; Hauri, Silke; Tettenborn, Annette; Hartmann, Erich; Näpflin, Catherine; Hugener, Isabelle; Niggli, Alois
Abstract: This study reviews the effectiveness of an extracurricular paired reading program to enhance the reading of struggling readers. For the first time, two program conditions are compared within one study: parent tutors and volunteer tutors. The program was implemented within a randomized controlled field trial; its effects on reading fluency and reading ability were investigated on a sample of 198 Swiss third graders with reading difficulties. The findings revealed that volunteers outperformed parents: Children who trained with volunteers developed significantly better reading fluency after 20 weeks ( d = .21). However, the main effects on reading fluency did not last at follow-up and no effects on general reading ability were found. Children with higher reading fluency at the pretest benefitted significantly more than very poor readers (post-test: d = .47; 5 month FU: d = .39). The study highlights the benefit of volunteer tutoring and the necessity of ongoing, adaptive support for very poor readers. Highlights: A paired reading program was implemented to enhance reading ability of 3rd graders. The randomized controlled trial included two conditions: parent and volunteer tutors. Students of the volunteer tutors' condition showed significant effects at posttest. Students with higher reading fluency benefitted more from training in both conditions. Implementation (no. of training sessions) did not predict nor moderate training success.